Monitoring Drug Safety in Pregnancy with Scan Statistics: A Comparison of Two Study Designs. Issue 1 (17th October 2022) - Suarez, Elizabeth A.; Nguyen, Michael; Zhang, Di; Zhao, Yueqin; Stojanovic, Danijela; Munoz, Monica; Liedtka, Jane; Anderson, Abby; Liu, Wei; Dashevsky, Inna; DeLuccia, Sandra; Menzin, Talia; et al.
Abstract : Background: Traditional surveillance of adverse infant outcomes following maternal medication exposures relies on pregnancy exposure registries, which are often underpowered. We characterize the statistical power of TreeScan, a data mining tool, to identify potential signals in the setting of perinatal medication exposures and infant outcomes. Methods: We used empirical data to inform background incidence of major congenital malformations and other birth conditions. Statistical power was calculated using two probability models compatible with TreeScan, Bernoulli and Poisson, while varying the sample size, magnitude of the risk increase, and incidence of a specified outcome. We also simulated larger referent to exposure matching ratios when using the Bernoulli model in the setting of fixed N:1 propensity score matching. Finally, we assessed the impact of outcome misclassification on power. Results: The Poisson model demonstrated greater power to detect signals than the Bernoulli model across all scenarios and suggested a sample size of 4, 000 exposed pregnancies is needed to detect a twofold increase in risk of a common outcome (approximately 8 per 1, 000) with 85% power. Increasing the fixed matching ratio with the Bernoulli model did not reliably increase power. An outcome definition with high sensitivity is expected to have somewhat greater power to detect signals than an outcome definition with high positive predictive value. Conclusions: Use of the Poisson model with an outcome definition that prioritizes sensitivity may be optimal for signal detection. TreeScan is a viable method for surveillance of adverse infant outcomes following maternal medication use.